Identification of new molecular markers for low glucosinolates in Indian mustard (Brassica juncea L. Czern and Coss.): Identification of new molecular markers for low glucosinolates in Indian mustard (Brassica juncea L. Czern and Coss.) - H D PUSHPA,; D K YADAVA,; SUJATA VASUDEV,; V VINU,; CHANDANABEHERA,; NAVEEN SINGH, (Journal of Oilseeds Research, 2020)
The study was carried out to identify molecular markers linked to low glucosinolates in Brassica juncea using recombinant inbred lines developed from cross between Pusa Mustard 21 × EC597325. Parental polymorphism studies with 594 SSR markers, revealed 62 informative markers. The bulk segregant analysis (BSA) revealed four microsatellite markers differentiating both the parental lines and the high and low glucosinolates bulks, hence putatively linked to the genomic regions controlling low glucosinolates.